Structures and mechanisms of CRISPR RNA-guided effector nucleases - Nishimasu, Hiroshi; Nureki, Osamu (Current opinion in structural biology, 2017)
[Display omitted] •Incredible structural and mechanistic diversity in the CRISPR-Cas effector nucleases.•Divergent evolution of the type I (Cascade-Cas3) and type III (Csm/Cmr) effector nucleases.•Functional convergence between the type II (Cas9) and type V (Cpf1) effector nucleases. In the prokaryotic CRISPR-Cas adaptive immune systems, a CRISPR RNA (crRNA) assembles with multiple or single Cas proteins to form crRNA ribonucleoprotein (crRNP) effector complexes, responsible for the destruction of invading genetic elements. Although the mechanisms of target recognition and cleavage by the crRNP effectors are quite diverse among the different types of CRISPR-Cas systems, the basic action principles of these crRNA-guided effector nucleases are highly conserved. In all of the crRNP effectors, the repeat-derived invariant and spacer-derived variable segments of the crRNA are recognized by the Cas protein(s) in sequence-dependent and sequence-independent manners, respectively, with the spacer-derived guide segment available for base pairing with target nucleic acids. Over the past few years, intensive studies have provided an atomic view of the crRNA-guided target interference mechanisms in different types of CRISPR-Cas systems. Here, we review the recent progress toward structural and mechanistic understanding of the diverse crRNP effector nucleases.